Can an individualized adherence education program delivered by nurses improve therapeutic adherence in elderly people with acute myocardial infarction?: A randomized controlled study. (August 2021) - Calvo, Elena; Izquierdo, Silvia; Castillo, Rocio; César, Elisabeth; Domene, Gerard; Gómez, Ana Belén; Guerrero, Carmen; Andreu-Periz, Lola; Gómez-Hospital, Joan Antoni; Ariza-Solé, Albert
Abstract: Background: The ageing of the population is leading to an increase in the number of elderly patients with acute myocardial infarction. These patients are at higher risk for complications and poor medication adherence, which in turn are associated with higher healthcare resource expenditures. Nursing programmes might help to improve adherence in these complex patients. Objective: The objective of this study was to assess the impact of a nursing intervention on therapeutic adherence in elderly patients after myocardial infarction compared to a control group. Design: A single-blind, randomized controlled trial. Settings: Heart disease institute of a tertiary care hospital. Participants: Patients aged ≥75 years with myocardial infarction undergoing percutaneous coronary intervention. Methods: A comprehensive geriatric assessment was performed during the admission in all patients (N=143). Patients were randomly allocated to a nursing intervention group (n=68) or a usual care group (n=75). In patients from the intervention group, a nursing intervention programme was performed 3 months after admission based on education support and patient monitoring to improve therapeutic adherence. The main outcome measured was 12-months therapeutic adherence, as defined by a combination of measurement tools (Morisky-Green and Hayness-Sacket scales, attendance at visits and withdrawal of medication from the pharmacy). Therapeutic adherence was assessed by nurses blinded to the assignment group. Results: The mean age was 82.2 years. The proportion of comorbidities was significant (diabetes mellitus 51/143 (35.7%), hypertension 110/143 (76.9%), prior stroke 22/143 (15.4%)). Likewise, the proportion of geriatric syndromes was noticeable (frailty 26/143 (18.2%), risk of malnutrition 38/143 (26.6%), cognitive impairment 28/143 (19.6%)). Most patients (92.3%) had a low educational level. A total of 119 patients achieved 12-month assessment adherence. Among these patients, the proportions of adherence were as follows: Morisky-Green test: 76/119 (63.9%), Haynes-Sackett test 99/119 (83.2%), medical visits compliance 95/119 (79.8%), and correct acquisition of drugs in the pharmacy 74/119 (62.2%). A total of 42/119 patients (35.3%) were adherent as defined by the combination of the 4 measures. Therapeutic adherence at 12 months was achieved in a significantly higher proportion of patients from the nursing intervention group (51.9% vs 21.5%, p<0.001). Conclusion: A significant proportion of elderly patients with myocardial infarction were non-adherent at 12 months. The proportion of adherent patients was highly variable according to the different tools used. A structured nursing intervention was independently associated with a higher adherence rate, as assessed by a multidimensional measurement, in this subset of complex high-risk elderly patients with myocardial infarction. Trial registration: Registered with www.clinicaltrials.gov (NCT04662762)